1978
DOI: 10.3109/03009747809095652
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Inflammatory Rheumatic Diseases in Finland

Abstract: The incidence of inflammatory joint diseases was estimated by using two patient series. Firstly, the total yearly incidence of all such diseases together was estimated in a population of 15 600 persons of 16 years of age or older. Secondly, this overall incidence was divided by the ratio of different diseases obtained from a larger series of patients. The incidence of all inflammatory joint diseases was 218/100 000/year, 182 in males and 250 in females. The incidence was highest in middle age and lowest in old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
1

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 7 publications
6
28
0
1
Order By: Relevance
“…We concluded that reactive arthritis may sometimes erroneously be diagnosed as rheumatoid arthritis. The same suggestion has been presented earlier by Isomaki et al (24) and by Calin and Marks (6). However, it is not excluded that in some cases reactive arthritis becomes chronic and leads into true rheumatoid arthritis.…”
supporting
confidence: 79%
“…We concluded that reactive arthritis may sometimes erroneously be diagnosed as rheumatoid arthritis. The same suggestion has been presented earlier by Isomaki et al (24) and by Calin and Marks (6). However, it is not excluded that in some cases reactive arthritis becomes chronic and leads into true rheumatoid arthritis.…”
supporting
confidence: 79%
“…Patients with ReA comprise about 10% of those presenting at early synovitis clinics (45,46). While no large analysis on the distribution of the background infections in patients with ReA has been undertaken, it seems evident that previously the most frequent triggering infections in hospital-based series were due to Yersinia and Chlamydia trachomatis (45,47).…”
Section: Hospital-based Series Of Reamentioning
confidence: 98%
“…A retrospective study in Heinola, Finland used several different strategies: hospital records, interviews of physicians, and official statistics, and reported the annual incidence of all arthritis in adults 218/100,000 (19). The incidence of definite rheumatoid arthritis in adults was 40.…”
Section: Discussionmentioning
confidence: 99%